Mini-Cog Performance. (January 2015) - Patel, Apurva; Parikh, Roosha; Howell, Erik H.; Hsich, Eileen; Landers, Steven H.; Gorodeski, Eiran Z.
<x xml:space="preserve">Abstract</x> Background— Heart failure (HF) guidelines recommend screening for cognitive impairment (CI) but do not identify how. The Mini-Cog is an ultrashort cognitive "vital signs" measure that has not been studied in patients hospitalized for HF. The purpose of this study was to evaluate whether CI as assessed by the Mini-Cog is associated with increased readmission or mortality risk after hospitalization for HF. Methods and Results— We analyzed 720 consecutive patients who completed the Mini-Cog as a part of routine clinical care during hospitalization for HF. Our primary outcome was time between hospital discharge and first occurrence of readmission or mortality. There was a high prevalence of CI as quantified by Mini-Cog performance (23% of cohort). During a mean follow-up time of 6 months, 342 (48%) patients were readmitted, and 24 (3%) died. Poor Mini-Cog performance was an independent predictor of composite outcome (adjusted hazard ratio, 1.90; 95% confidence interval, 1.47–2.44; P<0.0001) and was identified as the most important predictor among 55 variables by random survival forest analysis. Inclusion of Mini-Cog performance in risk models improved accuracy (bootstrapped c-index, 0.602 versus 0.624) and risk reclassification (category-free net reclassification improvement, 27%; 95% confidence interval, 14%–40%; P<0.001). Secondary analysis of initial 30 days post discharge showed effect modification by venue of discharge, whereby patients with CI discharged to a facility had longer time to outcome as compared with those discharged home. Conclusions— Mini-Cog performance is a novel marker of posthospitalization risk. Discharge to facility rather than home may be protective for those patients with HF and CI. It is unknown whether structured in-home support would yield similar outcomes.